Determinants of the development of the renewable energy market in Poland - Stanowicka, Agnieszka (Economics and Environment, 2025)
The aim of this study was to identify the conditions for the development of the renewable energy market in Poland in comparison with other European Union countries, and to highlight the opportunities and obstacles for the development of this sector of the economy. The article is a literature review, but in order to assess the development of the renewable energy market in Poland compared to other European countries, EU countries were grouped according to the average share and percentage change of energy from renewable sources in gross final energy consumption in 2017-2022. None of the countries reached a high level for either variable over the analysed period. One third of the EU countries are still underdeveloped in terms of renewable energy use. Poland was classified as a developing country in this respect. The main conditions for this status were divided into economic, social, political, legal and administrative, environmental and technological. The main obstacles to the development of renewable energy sources are of an economic nature, while environmental conditions and technological development offer opportunities for development.